SYNTHESIS, CHARACTERIZATION, BIOLOGICAL EVALUATION AND DOCKING OF SOME NOVEL SUBSTITUTED 1, 3-THIAZINE DERIVATIVES - Bairam, Ravindar; Muppavarapu, Srinivasa Murthy; Sreekanth, Sivan (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Chalcones and their heterocyclic analogs represent an important class of small molecules which have a wide range of pharmacological activities. Therefore, in this study, synthesis and anticonvulsant and antimicrobial activities of some new 1, 3-thiazines have been extensively discussed. Methods: The reaction mixture of 4-tert-butylcyclohexanone on Claisen-Schmidt condensation with various aromatic aldehydes in the presence of dilute sodium hydroxide afforded the corresponding chalcones. Further, these compounds were subjected to cocondensation with thiourea, in the presence of isopropanol, catalyzed by aqueous potassium hydroxide to form 4-aryl 8-arylidene-5, 6-dihydro-2-imino-6-methyl-4H, 7H-(1, 3) benzothiazines. The structures of the newly synthesized compounds have been established on the basis of their spectral analysis. The newly synthesized compounds have been tested for their biological screening. Antimicrobial activity by cup plate agar diffusion method and antiepileptic activity by pentylenetetrazole (PTZ) induced seizures model, using diphenyl hydantain as standard, and also they are subjected to molecular properties prediction, toxicity, drug-likeness, lipophilicity and solubility parameters determination were done by using Osiris program, Molsoft, Prototox and ALOGPS 2.1 software. The binding mode of the synthesized compounds with active protein site has been predicted using docking method. Results: Most of the compounds have shown good anticonvulsant as well as antimicrobial activities, but it is less than the standard drugs. 1, 3-thiazines derivatives were more potent, and among them, compounds TB5 andTB7 were the most active compounds in these series; TB5 whichcontains isopropyl phenyl moiety, was shown moderate potent activity with onset of convulsion at 14.1 min and TB7 containing 3, 4, 5-trimethoxyphenyl substituents on the thiazine moiety was more potent as it has prolonged the onset of convulsions by 18.7 min. Whereas in the case of antimicrobial activity of the compounds, from the results we have observed that TB5 have been shown greatest antimicrobial activity in all the bacterial and fungal strains, TB2 also shown superior activity, the others have been shown good antimicrobial activity. Conclusion: According to the activity studies, it is observed that the synthesis and antimicrobial as well as anticonvulsant activities of novel 1, 3-thiazine derivatives have been shown better activity. Moreover molecular docking results give an insight into how further modification of the lead compound can be carried out for higher inhibitory activity. In particular, compounds with electron withdrawing substituents along with lipophilic methoxyl and isopropyl groups were more potent.